Students’ Perception Toward E-Learning Experience On Writing Skill During Covid-19 Pandemic - Mister Gidion Maru; Jenerio Michal Mokal; Hesty Yuanita Saroinsong; Tini Mogea; Nihta Liando (Syntax Corporation, 2022)
This research aims to examine students’ perception towards e-learning experience on writing skills during the Covid-19 pandemic, specifically in the advance writing course. The qualitative design has been conducted with thirty participants at English Education Department Manado State University. They are chosen based on several criteria such as (1) participants are English students, (2) participants have studied advanced writing courses in an e-learning environment, and (3) participants have experience e-learning without internet access distraction during the e-learning process. The responses were collected through a modified online questionnaire which are later statistically interpreted. The finding leads to the conclusion that the majority of the participants had a positive perception toward e-learning experience on writing skills during the covid-19 pandemic in terms of the learning process, learning outcome, and learning evaluation, although there was minor disagreement by the few participants. It explicitly revealed that the e-learning activity could contribute to assist the learning needs such as comfortableness, flexibility, accessibility, interaction, easiness, and feedback. The overall discussion leads the researcher to suggest further researches on figuring out roles of learning communities and groups, and effective assessment and evaluation on online writing courses.